Additional radiation effect on cell viability using neutron irradiated Cisplatin and Carboplatin: preliminary results - Alexandre Soares Leal; Juliana B Silva; Ana Olivia G Morais; Brigida Gomes de Almeida Schirmer (Brazilian Journal of Radiation Sciences, 2025)
The objective of this work was to investigate the effect on cell viability of radiolabeled complexes of cisplatin and carboplatin in cancer cells of the 4T1 and MDA-MB-231 lines from mice with mammary carcinoma. The complexes were labeled in the CDTN's TRIGA Mark I nuclear research reactor after 3 hours of irradiation. The analyzes were carried out after decay times of 1h and 24h. The results showed a more effective action of cisplatin compared to carboplatin in both cell lines and greater resistance in MDA-MB-231 cells. The additional effect of radiation was more evident in conditions of low resistance. Increasing the final activity of labeled compounds can amplify this effect. Investigations in this regard are underway.